Immune thrombocytopenia associated with lymph node tuberculosis: a case report - Juliano Córdova Vargas; Patrícia Nunes Bezerra; Murilo Sequeira; Gabriella Haydée de Oliveira; Carlos Eduardo Pegolo; Lucas Fiore; Nelson Hamerschlak; Paulo Roberto Abrão Ferreira (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Extrapulmonary tuberculosis associated with immune thrombocytopenia (ITP) is extremely rare. A likely association between ITP and pulmonary and lymph node tuberculosis was reported in a 29-year-old male patient. His platelet count decreased to 4,000/µL. Chest tomography revealed mediastinal adenomegaly, lymph node clusters in the aorta, and consolidation in the left upper lung lobe. Immunoglobulin and methylprednisolone were administered intravenously. The histopathology of the left upper lung lobe confirmed tuberculosis. The rifampicin/isoniazid/pyrazinamide/ethambutol regimen was initiated, and the corticosteroids were tapered off. This case suggests an association of tuberculosis with ITP, since the platelet count effectively normalized after tuberculosis treatment.